Non-aqueous electrolyte, and non-aqueous electrolyte battery using that non-aqueous electrolyte

JP2023024397A5Pending Publication Date: 2025-03-25MU IONIC SOLUTIONS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022125415
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-08-06
Filing Date
2022-08-05
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing non-aqueous electrolyte solutions for batteries suffer from a fragile negative electrode film and side reactions that decrease the recovery capacity retention rate, as observed in prior art technologies.

Method used

Incorporation of specific cyclic sulfur-containing compounds, phosphate anion-containing compounds with P-F and P=O bonds, and oxalate complex anions into the non-aqueous electrolyte, forming a poorly soluble and strong co-film on the electrode surface to suppress side reactions.

Benefits of technology

The proposed solution significantly improves the recovery capacity retention rate and minimizes gas generation during high-temperature storage, enhancing the performance of non-aqueous electrolyte batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2023024397000001
    Figure 2023024397000001
  • Figure 2023024397000002
    Figure 2023024397000002
Patent Text Reader

Abstract

To provide a non-aqueous electrolyte that can enhance the recovery capacity retention.SOLUTION: A non-aqueous electrolyte contains an electrolyte, a compound (A) represented by formula (I), and one or more anion-containing compounds (B) selected from the group consisting of phosphate anion-containing compounds having a P-F bond and a P=O bond, anion-containing compounds having an S=O bond, and oxalate complex anion-containing compounds. The content of the anion-containing compounds (B) in the electrolyte is from 0.001 mass% to 5 mass% inclusive.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a non-aqueous electrolyte solution and a non-aqueous electrolyte battery using the non-aqueous electrolyte solution. [Background technology]

[0002] Energy devices typified by nonaqueous electrolyte batteries such as lithium ion secondary batteries are being put to practical use in a wide range of applications, from so-called consumer power sources for mobile phones, laptop computers, etc. to on-board power sources for driving automobiles, etc. However, in recent years, there has been an increasing demand for higher performance for nonaqueous electrolyte batteries, and in particular, there has been a demand for improvements in various battery characteristics such as higher capacity, low-temperature usage characteristics, high-temperature storage characteristics, cycle characteristics, and safety during overcharge. To date, numerous technologies have been investigated for various battery components, including the active materials of the positive and negative electrodes and the nonaqueous electrolyte, as means for improving the high-temperature storage characteristics and cycle characteristics of nonaqueous electrolyte secondary batteries.

[0003] Patent Document 1 discloses a nonaqueous electrolyte solution for a lithium ion secondary battery that contains a specific vinylene carbonate compound and a specific vinylethylene sulfite in order to provide a lithium ion secondary battery that suppresses gas generation during continuous charging and has excellent discharge characteristics after continuous charging. Patent Document 2 discloses a nonaqueous electrolyte secondary battery containing 2 mass % or less of a specific cyclic unsaturated sultone compound and 2 mass % or less of a specific cyclic sulfite ester as the nonaqueous electrolyte, in order to provide a nonaqueous electrolyte secondary battery that suppresses an increase in the internal resistance of the battery after high-temperature storage and that suppresses an increase in the internal resistance of the battery when the battery is used at a low temperature after high-temperature storage. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Laid-Open No. 2005-166553 [Patent Document 2] Japanese Patent Application Laid-Open No. 2010-92698 Summary of the Invention [Problem to be solved by the invention]

[0005] The present inventors have found that the nonaqueous electrolyte solutions described in Patent Documents 1 and 2 have problems in that the negative electrode coating formed on the negative electrode is brittle, side reactions of the nonaqueous electrolyte solution occur on the negative electrode, and improvement in the recovered capacity retention rate is insufficient.

[0006] The present invention has been made to solve the above problems, and an object of the present invention is to provide a nonaqueous electrolyte solution that can improve the recovered capacity maintenance rate when used in a nonaqueous electrolyte battery, and a nonaqueous electrolyte battery that uses the nonaqueous electrolyte solution. [Means for solving the problem]

[0007] In view of the above circumstances, the present inventors have conducted extensive research and found that the above problems can be solved by using a nonaqueous electrolyte solution containing a specific cyclic sulfur-containing compound and one or more anion-containing compounds selected from the group consisting of a phosphate anion-containing compound having a P-F bond and a P=O bond, an anion-containing compound having an S=O bond, and an oxalate complex anion-containing compound, in specific amounts, and have thus completed the present invention. That is, the gist of the present invention is as follows.

[0008] [1] A non-aqueous electrolyte solution comprising a compound (A) represented by formula (I) and one or more anion-containing compounds (B) selected from the group consisting of phosphate anion-containing compounds having a P-F bond and a P=O bond, anion-containing compounds having an S=O bond, and oxalate complex anion-containing compounds, wherein the content of the anion-containing compound (B) in the electrolyte solution is 0.001% by mass or more and 5% by mass or less.

[0009] [ka] (In formula (I), X 1 and X 2 are each independently an oxygen atom or CH, and R 1 and R 2 are each independently a hydrogen atom, a halogen atom, or a hydrocarbon group, and n is 1 or 2. 1 and R 2 is a hydrocarbon group containing at least one carbon-carbon unsaturated bond, and when n is 2, X 1 and X 2 At least one of these is CH2.)

[0010] [2] The nonaqueous electrolyte solution according to [1], wherein the compound (A) is a compound represented by the following formula (II):

[0011] [ka] (In formula (II), R 1 and R 2 represents R in the formula (I). 1 and R 2 is the same as [3]R 1 and R 2 are each independently one selected from a hydrogen atom, a halogen atom, a vinyl group, or an allyl group, and R 1 and R 2 wherein either one of the groups is selected from a vinyl group and an allyl group. [4] The nonaqueous electrolyte solution according to any one of [1] to [3], which contains the compound (A) in an amount of 0.01 mass % or more and 10 mass % or less. [5] The nonaqueous electrolyte solution according to any one of [1] to [4], further containing a chain carboxylic acid ester. [6] The nonaqueous electrolyte solution according to [5], wherein the chain carboxylic acid ester is methyl acetate or methyl propionate. [7] The nonaqueous electrolyte solution according to either [5] or [6], wherein the content of the chain carboxylic acid ester in the nonaqueous solvent is 1% by volume or more and 70% by volume or less. [8] A nonaqueous electrolyte battery comprising: a positive electrode having a positive electrode active material capable of absorbing and releasing metal ions; a negative electrode having a negative electrode active material capable of absorbing and releasing metal ions; and the nonaqueous electrolyte solution according to any one of [1] to [7]. [Effects of the Invention]

[0012] According to the present invention, it is possible to provide a nonaqueous electrolyte solution that can improve the recovered capacity maintenance rate when used in a nonaqueous electrolyte battery, and also to provide a nonaqueous electrolyte battery including the nonaqueous electrolyte solution. DETAILED DESCRIPTION OF THE INVENTION

[0013] [1. Non-aqueous electrolyte] The nonaqueous electrolyte solution of the present invention is a nonaqueous electrolyte solution for a nonaqueous electrolyte battery, The nonaqueous electrolytic solution contains an electrolyte, a compound (A) represented by formula (I) (hereinafter also referred to as "compound (A)"), and at least one anion-containing compound (B) (hereinafter also referred to as "anion-containing compound (B)") selected from the group consisting of phosphate anion-containing compounds having a P-F bond and a P=O bond, anion-containing compounds having an S=O bond, and oxalate complex anion-containing compounds, wherein the content of the anion-containing compound (B) in the electrolytic solution is 0.001% by mass or more and 5% by mass or less.

[0014] The inventors speculate that the reason why the nonaqueous electrolyte having the configuration of the present invention exhibits such excellent effects is as follows. During charge and discharge of a nonaqueous electrolyte battery, the carbon-carbon unsaturated bonds of compound (A), preferably those contained in an aliphatic group, react on the electrode, causing compound (A) to polymerize. The polymerized compound (A) then reacts with anion-containing compound (B), forming a poorly soluble and strong co-coating film on the electrode that contains an S═O bond and a structure derived from the anion-containing compound (B). This suppresses side reactions between the electrode active material and the solvent, etc. The poorly soluble and strong co-coating film on the electrode that contains an S═O bond and a structure derived from the anion-containing compound (B) significantly suppresses side reactions between the electrode active material and the solvent, etc., compared to a coating made of a polymer of a compound that contains a carbon-carbon unsaturated bond but does not contain an S═O bond, or a coating that does not contain a structure derived from the anion-containing compound (B).

[0015] [1-1. Compound (A) represented by formula (I)]

[0016] [ka]

[0017] In formula (I), X 1 and X 2 are each independently an oxygen atom or CH, and R 1 and R 2 are each independently a hydrogen atom, a halogen atom, or a hydrocarbon group, and n is 1 or 2. 1 and R 2 is a hydrocarbon group containing at least one carbon-carbon unsaturated bond, and when n is 2, X 1 and X 2 At least one of these is CH2.

[0018] Among these, X 1 is an oxygen atom, X 2 is an oxygen atom and n is 1; X is a sulfite ester structure 1 is an oxygen atom, X 2is a sulfonate ester structure in which X is CH2 and n is 2; 1 is an oxygen atom, X 2 A sulfite ester structure in which is an oxygen atom and n is 1 is more preferred.

[0019] R 1 and R 2 Either one of R is a hydrocarbon group containing at least one carbon-carbon unsaturated bond. Examples of hydrocarbon groups containing at least one carbon-carbon unsaturated bond include alkenyl groups having 2 to 8 carbon atoms, alkynyl groups having 2 to 8 carbon atoms, aryl groups having 4 to 12 carbon atoms, and aralkyl groups having 7 to 10 carbon atoms. Aryl groups and aralkyl groups include heteroaryl groups and heteroaralkyl groups in which any carbon atom constituting an aromatic ring is replaced with a heteroatom. R 1 , R 2 When is a hydrocarbon group containing a carbon-carbon unsaturated bond, it is preferably an alkenyl group having 2 to 8 carbon atoms or an alkynyl group having 2 to 8 carbon atoms, more preferably an alkenyl group having 2 to 8 carbon atoms. R 1 and R 2 When the hydrocarbon group is a saturated hydrocarbon group, examples of the hydrocarbon group include alkyl groups having 1 to 10 carbon atoms.

[0020] Examples of the alkenyl group include a vinyl group, an allyl group, a methallyl group, a 2-butenyl group, a 3-methyl-2-butenyl group, a 3-butenyl group, a 4-pentenyl group, a 5-hexenyl group, a 6-heptenyl group, and a 7-octenyl group. Among these, from the viewpoint of solubility in an electrolyte, an alkenyl group having 2 to 6 carbon atoms is preferred, and a vinyl group and an allyl group are more preferred.

[0021] Examples of the alkynyl group include an ethynyl group, a 2-propynyl group, a 2-butynyl group, a 3-butynyl group, a 4-pentynyl group, a 5-hexynyl group, a 6-heptynyl group, and a 7-octynyl group. Among these, from the viewpoint of solubility in an electrolyte, an alkynyl group having 2 to 6 carbon atoms is preferred, and an ethynyl group is more preferred.

[0022] Examples of the aryl group include a phenyl group, a 1-naphthyl group, a 2-naphthyl group, a 2-thienyl group, a 3-thienyl group, a 2-furyl group, a 3-furyl group, a 2-pyrrolyl group, a 3-pyrrolyl group, and a benzyl group. Among these, from the viewpoint of solubility in an electrolyte, an aryl group having 6 to 12 carbon atoms is preferred, and a phenyl group is more preferred.

[0023] Examples of the aralkyl group include a benzyl group, a phenethyl group, a phenylpropyl group, a phenylbutyl group, and a phenylisopropyl group. Among these, from the viewpoint of solubility in the electrolyte, a benzyl group and a phenethyl group are preferred, and a benzyl group is more preferred.

[0024] Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a tert-butyl group, an n-pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, and a decyl group. Among these, from the viewpoint of solubility in an electrolyte, an alkyl group having 1 to 6 carbon atoms is preferred, and a methyl group, an ethyl group, and an isopropyl group are more preferred.

[0025] R in formula (I) 1 and R 2 may be bonded to form a cyclic structure. Examples of the cyclic structure include unsaturated carbon rings excluding aromatic rings such as a cyclohexene ring and a cyclopentene ring. Among these, a cyclohexene ring is preferred from the viewpoint of stability in an electrolyte solution.

[0026] Also, R 1 or R 2 When is a hydrocarbon group, a carbon atom in the hydrocarbon group may be substituted with an oxygen atom, and a hydrogen atom may be substituted with a halogen atom, such as a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom.

[0027] Since compound (A) tends to react and polymerize on the electrode, R 1 and R 2are preferably each independently one selected from a hydrogen atom, a halogen atom, a vinyl group, and an allyl group, and R 1 and R 2 is selected from a vinyl group and an allyl group. 1 and R 2 A combination in which one of the above is a vinyl group and the other is a hydrogen atom is preferred.

[0028] Among the compounds (A) represented by formula (I), X 1 is an oxygen atom, X 2 A compound represented by the following formula (II), which has a sulfite structure in which is an oxygen atom and n is 1, is preferred.

[0029] [ka]

[0030] In formula (II), R 1 and R 2 is R in formula (I). 1 and R 2 is synonymous with.

[0031] Specific examples of the compound represented by formula (II) include compounds represented by the following structural formulas.

[0032] [ka]

[0033] [ka]

[0034] [ka]

[0035] Among the above compounds, the compound represented by formula (II) is preferably a compound represented by the following structural formula:

[0036] [ka]

[0037] Among the compounds represented by the above formula (II), more preferred are compounds represented by the following structural formulas.

[0038] [ka]

[0039] Among the compounds represented by the above formula (II), more preferred are compounds represented by the following structural formulas.

[0040] [ka]

[0041] Among the compounds represented by the above formula (II), particularly preferred are compounds represented by the following structural formulas.

[0042] [ka]

[0043] Among the compounds represented by the above formula (II), the most preferred are compounds represented by the following structural formula.

[0044] [ka]

[0045] Specific examples of the compound (A) represented by formula (I) other than the compound represented by formula (II) are shown below.

[0046] In formula (I), X 1 is CH2, X 2Specific examples of compounds having a sulfone structure where is CH2 and n is 2 include compounds represented by the following structural formulas.

[0047] [ka]

[0048] In formula (I), X 1 is an oxygen atom, X 2 Specific examples of compounds having a sulfonate structure in which is CH2 and n is 2 include compounds represented by the following structural formulas.

[0049] [ka]

[0050] In formula (I), X 1 is CH2, X 2 Specific examples of compounds having a sulfonate structure in which is an oxygen atom and n is 2 include compounds represented by the following structural formulas.

[0051] [ka]

[0052] (Content of Compound (A)) The content of compound (A) in the total amount (100% by mass) of the nonaqueous electrolyte is usually 0.01% by mass or more, preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and usually 10% by mass or less, preferably 8% by mass or less, more preferably 6% by mass or less, and even more preferably 4% by mass or less. When the content of compound (A) is within this range, the generation of initial gas and the generation of gas after high-temperature storage in a nonaqueous electrolyte battery can be suppressed. Compound (A) may be used alone, or two or more types may be used in any combination and ratio. The identification and content of compound (A) are measured by nuclear magnetic resonance (NMR) spectroscopy and / or gas chromatography.

[0053] (Mass ratio of compound (A) to electrolyte) In the nonaqueous electrolyte, the mass ratio of the content of compound (A) (total amount when two or more types are used) to the content of the electrolyte (compound (A) [g] / electrolyte [g]) is usually 0.001 or more, preferably 0.01 or more, more preferably 0.02 or more, even more preferably 0.025 or more, and even more preferably 0.03 or more, and is usually 0.5 or less, preferably 0.3 or less, more preferably 0.2 or less, and even more preferably 0.1 or less. If the mass ratio is within this range, battery characteristics, particularly the recovered capacity retention rate, can be significantly improved. Although the mechanism behind this effect is unclear, it is thought that by setting the mass ratio of the content of compound (A) to the content of the electrolyte within this range, side reactions of the electrolyte in the battery system are minimized.

[0054] [1-2. Anion-containing compounds (B)] The anion-containing compound (B) is selected from a phosphate anion-containing compound having a PF bond and a P=O bond, an anion-containing compound having an S=O bond, and an oxalate complex anion-containing compound. The anion-containing compound (B) may be used alone or in any combination and ratio of two or more. Among these, from the viewpoint of improving the recovered capacity retention rate, a phosphate anion-containing compound having a P-F bond and a P=O bond or an anion-containing compound having an S=O bond is preferred, and a difluorophosphate anion-containing compound or a fluorosulfonate anion-containing compound is more preferred. In order to suppress the amount of gas generated during high-temperature storage, the anion-containing compound (B) is preferably a phosphate anion-containing compound or an oxalate complex anion-containing compound having a PF bond and a P=O bond, more preferably a difluorophosphate anion-containing compound or a boron oxalate complex anion-containing compound. Furthermore, in order to suppress the deterioration of DCR, the anion-containing compound (B) is even more preferably a phosphate anion-containing compound having a PF bond and a P=O bond.

[0055] [1-2-1. Phosphate anion-containing compounds with PF bonds and P=O bonds] The phosphate anion-containing compound having a PF bond and a P=O bond is not particularly limited as long as it is a compound containing an anion derived from phosphoric acid and having a PF bond and a P=O bond in the molecule. Examples of phosphoric acid having a PF bond and a P=O bond include monofluorophosphoric acid represented by the molecular formula H2PO3F and difluorophosphoric acid represented by the molecular formula HPO2F2. Counter cations of the phosphate anion having a P—F bond and a P═O bond include cations of alkali metals such as lithium, sodium, and potassium, with the lithium cation being preferred. Examples of salts of phosphate anions having a P-F bond and a P=O bond include salts of monofluorophosphate anions such as Li2PO3F; and salts of difluorophosphate anions such as LiPO2F2, NaPO2F2, and KPO2F2. In particular, from the viewpoint of the balance between the output characteristics of the battery and the protection of the electrode interface, salts of difluorophosphate anions are preferred, and lithium difluorophosphate is more preferred.

[0056] [1-2-2. Anion-containing compounds with S=O bonds] The anion-containing compound having an S=O bond is not particularly limited as long as it has an S=O bond in the molecule, and any compound can be used as long as it does not significantly impair the effects of the present invention. Examples of acids containing an anion having an S=O bond include fluorosulfonic acid represented by the molecular formula HSO3F, fluorosulfonylimide represented by the molecular formula HN(FSO2), fluorosulfonylmethide represented by the molecular formula HC(FSO2)3, and alkyl sulfates such as CH3SO4H. Counter cations of anions with S=O bonds include cations of alkali metals such as lithium, sodium, and potassium, as well as (CH3)4N + , (C2H5)4N + , FSO3(n-C4H9)4N + Among these, lithium cation is preferred. Examples of salts of anions having an S=O bond include salts of fluorosulfonic acid anions such as LiSO3F, NaSO3F, KSO3F, (CH3)4NSO3F, (C2H5)4NSO3F, and (n-C4H9)4NSO3F; salts of fluorosulfonylimide anions such as LiN(FSO2)2 and LiN(FSO2)(CF3SO2); salts of fluorosulfonylmethide anions such as LiC(FSO2)3; and salts of alkylsulfate anions such as LiCH3SO4 and LiC2H5SO4. In particular, from the viewpoint of the balance between the output characteristics of the battery and the protection of the electrode interface, salts of fluorosulfonic acid anions or salts of fluorosulfonylimide anions are preferred, salts of fluorosulfonic acid anions are more preferred, and lithium fluorosulfonate is even more preferred.

[0057] [1-2-3. Compounds containing oxalate complex anions] The oxalate complex anion-containing compound used in the present invention is not particularly limited as long as it is an anion-containing compound having an oxalate complex in the molecule. The oxalate complex anion is an anion of an acid in which oxalic acid is coordinated or bonded to the central atom to form a complex, and examples thereof include boron oxalate complex anions in which oxalic acid is coordinated or bonded to a boron atom, such as bis(oxalate)borate and difluorooxalateborate, and phosphorus oxalate complex anions in which oxalic acid is coordinated or bonded to a phosphorus atom, such as tris(oxalate)phosphate, difluorobis(oxalate)phosphate and tetrafluorooxalatephosphate. Counter cations of the oxalate complex anion include cations of alkali metals such as lithium, sodium, and potassium, with the lithium cation being preferred. Examples of salts of oxalate complex anions include salts of boron oxalate complex anions such as lithium bis(oxalate)borate and lithium difluorooxalateborate; and salts of phosphorus oxalate complex anions such as lithium tetrafluorooxalate phosphate, lithium difluorobis(oxalate)phosphate, and lithium tris(oxalate)phosphate. In particular, from the viewpoint of forming a stable co-coating film on the surface of the electrode, salts of boron oxalate complex anions are preferred, and lithium bis(oxalate)borate is more preferred.

[0058] (Content of anion-containing compound (B)) The content of the anion-containing compound (B) (total amount when two or more types are used) in the total amount (100% by mass) of the nonaqueous electrolyte is 0.001% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and 5% by mass or less, preferably 4% by mass or less, more preferably 3.5% by mass or less. When the content of the anion-containing compound (B) is within this range, battery characteristics, particularly the recovered capacity retention rate, can be significantly improved. While the mechanism behind this effect is unclear, it is believed to be due to the fact that when the content of the anion-containing compound (B) is within this range, side reactions of the components of the nonaqueous electrolyte on the electrode can be minimized. The anion-containing compound (B) is identified and its content measured using nuclear magnetic resonance (NMR) spectroscopy and / or ion chromatography.

[0059] (Mass ratio of anion-containing compound (B) to compound (A)) The mass ratio of the content of anion-containing compound (B) (total amount when two or more compounds are used) to the content of compound (A) (anion-containing compound (B) [g] / compound (A) [g]) is usually 0.01 or more, preferably 0.05 or more, more preferably 0.3 or more, and usually 100 or less, preferably 30 or less, more preferably 10 or less, more preferably 8 or less, and even more preferably 5.5 or less. If the mass ratio is within this range, battery characteristics, particularly recovered capacity retention rate, can be significantly improved. Although the mechanism behind this is unclear, it is thought that by containing compound (A) and anion-containing compound (B) within this mass ratio range, side reactions of the components of the nonaqueous electrolyte on the electrode can be minimized.

[0060] (Mass ratio of anion-containing compound (B) to LiPF6) In a nonaqueous electrolyte solution, when the electrolyte contains LiPF6, the mass ratio of the content of the anion-containing compound (B) (total amount when two or more types are used) to the content of LiPF6 (anion-containing compound (B) [g] / LiPF6 [g]) is usually 0.00005 or more, preferably 0.001 or more, more preferably 0.01 or more, even more preferably 0.02 or more, and even more preferably 0.025 or more, and usually 0.5 or less, preferably 0.45 or less, more preferably 0.4 or less, and even more preferably 0.35 or less. A mass ratio within this range can significantly improve battery characteristics, particularly the recovered capacity retention rate. While the mechanism behind this effect is unclear, it is thought that by containing the anion-containing compound (B) and LiPF6 within this mass ratio range, side reactions of LiPF6 within the battery system are minimized.

[0061] [1-3. Electrolytes] Examples of the electrolyte for the non-aqueous electrolytic solution include lithium salts. The lithium salt is not particularly limited and any one can be used, but examples thereof include lithium fluoroborates, lithium fluorophosphates, lithium tungstates, lithium carboxylates, lithium sulfonates, lithium imide salts, lithium methide salts, lithium oxalates, and fluorine-containing organic lithium salts.

[0062] Among these, from the viewpoint of improving low-temperature output characteristics, high-rate charge / discharge characteristics, impedance characteristics, high-temperature storage characteristics, cycle characteristics, etc., preferred are LiBF4 as the lithium fluoroborate salt; LiPF6 as the lithium fluorophosphate salt; LiCH3SO3 as the lithium sulfonate salt; LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium cyclic 1,2-perfluoroethanedisulfonylimide, lithium cyclic 1,3-perfluoropropanedisulfonylimide as the lithium imide salt; and LiC(CF3SO2)3, LiC(C2F5SO2)3, etc. as the lithium methide salt, with LiPF6 being more preferred.

[0063] The electrolytes can be used alone or in combination of two or more kinds in any ratio. The combination of two or more electrolytes is not particularly limited, and examples include a combination of LiPF6 and LiBF4, a combination of LiPF6 and LiN(CF3SO2)2, etc. Among these, the combination of LiPF6 and LiBF4 is preferred.

[0064] The total concentration of the electrolyte is not particularly limited, but from the viewpoint of ensuring that the electrical conductivity ensures proper battery operation and sufficient output characteristics, it is usually 8% by mass or more, preferably 8.5% by mass or more, more preferably 9% by mass or more, and usually 18% by mass or less, preferably 17% by mass or less, more preferably 16% by mass or less, based on the total amount of the nonaqueous electrolyte. The electrolyte is identified and its content is measured using nuclear magnetic resonance (NMR) spectroscopy and / or ion chromatography.

[0065] [1-4. Non-aqueous solvents] The non-aqueous electrolyte solution contains a non-aqueous solvent, similar to common non-aqueous electrolyte solutions. There are no particular limitations on the non-aqueous solvent as long as it dissolves the above-mentioned electrolyte, and known organic solvents can be used. Examples of the organic solvent include, but are not limited to, saturated cyclic carbonates, chain carbonates, chain carboxylic acid esters, cyclic carboxylic acid esters, cyclic ether compounds, and sulfone compounds.

[0066] The organic solvents can be used alone or in combination of two or more kinds in any ratio. Examples of combinations of two or more organic solvents include a combination of a saturated cyclic carbonate and a chain carbonate, a combination of a cyclic carboxylic acid ester and a chain carbonate, and a combination of a saturated cyclic carbonate, a chain carbonate and a chain carboxylic acid ester, etc. Among these, a combination of a saturated cyclic carbonate and a chain carbonate, and a combination of a saturated cyclic carbonate, a chain carbonate and a chain carboxylic acid ester are preferred, a combination of a saturated cyclic carbonate, a chain carbonate and a chain carbonate ester is more preferred, and a combination of a saturated cyclic carbonate, a chain carbonate and methyl acetate or methyl propionate is even more preferred, and a combination of a saturated cyclic carbonate, a chain carbonate and methyl acetate is even more preferred.

[0067] [1-4-1. Saturated cyclic carbonates] Examples of saturated cyclic carbonates include those having an alkylene group having 2 to 4 carbon atoms. From the viewpoint of improving battery characteristics resulting from an improved degree of dissociation of metal ions, particularly lithium ions, saturated cyclic carbonates having an alkylene group having 2 to 3 carbon atoms are preferred. Specific examples of saturated cyclic carbonates include ethylene carbonate, propylene carbonate, butylene carbonate, etc. Among these, ethylene carbonate or propylene carbonate is preferred, and ethylene carbonate, which is less susceptible to oxidation and reduction, is more preferred. The saturated cyclic carbonates can be used alone or in combination of two or more in any ratio.

[0068] The content of the saturated cyclic carbonate is not particularly limited and may be any content as long as it does not impair the effects of the present invention. The content of the saturated cyclic carbonate is usually 3% by volume or more, preferably 5% by volume or more, and more preferably 10% by volume or more, based on the total amount of the nonaqueous solvent, and is usually 90% by volume or less, preferably 85% by volume or less, and more preferably 80% by volume or less. By setting the content within this range, a decrease in electrical conductivity due to a decrease in the dielectric constant of the nonaqueous electrolyte solution can be avoided, and the large-current discharge characteristics, negative electrode stability, and cycle characteristics of the nonaqueous electrolyte battery tend to be in good ranges, and the oxidation / reduction resistance of the nonaqueous electrolyte solution and stability during high-temperature storage tend to be improved. In this specification, "volume %" refers to volume % at 25°C and 1 atmosphere.

[0069] [1-4-2. Chain carbonate] Examples of the chain carbonate include chain carbonates having 3 to 7 carbon atoms, and chain carbonates having 3 to 5 carbon atoms are preferred in order to adjust the viscosity of the non-aqueous electrolyte solution to an appropriate range. Specific examples of the chain carbonate include dimethyl carbonate, diethyl carbonate, di-n-propyl carbonate, diisopropyl carbonate, n-propyl isopropyl carbonate, ethyl methyl carbonate, methyl-n-propyl carbonate, etc. Among these, one or more selected from dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate are preferred, and dimethyl carbonate and a combination of dimethyl carbonate and ethyl methyl carbonate are more preferred. Furthermore, chain carbonates having fluorine atoms (hereinafter also referred to as "fluorinated chain carbonates") can also be suitably used. The number of fluorine atoms in the fluorinated chain carbonate is not particularly limited as long as it is 1 or more, but is preferably 6 or less, more preferably 4 or less. When the fluorinated chain carbonate has multiple fluorine atoms, the multiple fluorine atoms may be bonded to the same carbon or different carbons. Examples of the fluorinated chain carbonate include fluorinated dimethyl carbonate derivatives such as fluoromethyl methyl carbonate; fluorinated ethyl methyl carbonate derivatives such as 2-fluoroethyl methyl carbonate; and fluorinated diethyl carbonate derivatives such as ethyl-(2-fluoroethyl) carbonate. The chain carbonates can be used alone or in combination of two or more kinds in any ratio.

[0070] The content of the chain carbonate is not particularly limited, but from the viewpoint of keeping the viscosity of the nonaqueous electrolyte solution within an appropriate range, suppressing a decrease in ionic conductivity, and ultimately improving the output characteristics of the nonaqueous electrolyte battery, the content is usually 15% by volume or more, preferably 20% by volume or more, and more preferably 25% by volume or more, relative to the total amount of nonaqueous solvent in the nonaqueous electrolyte solution, and is usually 90% by volume or less, preferably 85% by volume or less, and more preferably 80% by volume or less.

[0071] Furthermore, by combining a specific chain carbonate with ethylene carbonate in a specific content, the battery performance can be significantly improved. For example, when dimethyl carbonate and ethyl methyl carbonate are selected as the specific chain carbonates, the content of ethylene carbonate, relative to the total amount of solvent in the non-aqueous electrolyte solution, from the viewpoint of improving high-temperature stability and suppressing gas generation, is usually 15% by volume or more, preferably 20% by volume or more, more preferably 25% by volume or more, and usually 45% by volume or less, preferably 40% by volume or less, more preferably 35% by volume or less; the content of dimethyl carbonate, relative to the total amount of non-aqueous solvent in the non-aqueous electrolyte solution, is usually 15% by volume or more, preferably 20% by volume or more, more preferably 25% by volume or more, and usually 50% by volume or less, preferably 45% by volume or less, more preferably 40% by volume or less; and the content of ethyl methyl carbonate, relative to the total amount of non-aqueous solvent in the non-aqueous electrolyte solution, is usually 20% by volume or more, preferably 30% by volume or more, and usually 50% by volume or less, preferably 45% by volume or less.

[0072] [1-4-3. Chain carboxylic acid esters] Examples of chain carboxylic acid esters include methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, methyl valerate, methyl isobutyrate, ethyl isobutyrate, and methyl pivalate. Among these, from the viewpoint of improving battery characteristics, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, and propyl propionate are preferred, and methyl acetate and methyl propionate are more preferred. Chain carboxylic acid esters in which some of the hydrogen atoms of the above compounds are substituted with fluorine atoms (e.g., methyl trifluoroacetate, ethyl trifluoroacetate, etc.) can also be suitably used. When a chain carboxylic acid ester is contained, its content is usually 1% by volume or more, preferably 5% by volume or more, and more preferably 15% by volume or more, based on the total amount of the nonaqueous solvent, from the viewpoints of improving the electrical conductivity of the nonaqueous electrolyte and enhancing the large-current discharge characteristics of the nonaqueous electrolyte battery. The upper limit of the content is usually 70% by volume or less, preferably 50% by volume or less, and more preferably 40% by volume or less, from the viewpoints of maintaining an appropriate viscosity of the nonaqueous electrolyte, avoiding a decrease in electrical conductivity, suppressing an increase in negative electrode resistance, and ensuring good large-current discharge characteristics of the nonaqueous electrolyte battery. The content of the chain carboxylic acid ester relative to the total amount of the non-aqueous solvent, calculated on a mass basis, is usually 0.8 mass% or more, preferably 4 mass% or more, more preferably 13 mass% or more, and is usually 63 mass% or less, preferably 44 mass% or less, more preferably 35 mass% or less.

[0073] [1-3-4. Cyclic carboxylic acid esters] Examples of cyclic carboxylic acid esters include γ-butyrolactone and γ-valerolactone. Among these, γ-butyrolactone is more preferred. Cyclic carboxylic acid esters in which some of the hydrogen atoms of the above compounds are substituted with fluorine atoms can also be used suitably. When the nonaqueous electrolyte solution contains a cyclic carboxylic acid ester, its content is usually 1% by volume or more, preferably 5% by volume or more, and more preferably 15% by volume or more, based on the total amount of the nonaqueous solvent, from the viewpoint of improving the electrical conductivity of the nonaqueous electrolyte solution and enhancing the large-current discharge characteristics of the nonaqueous electrolyte battery. The upper limit of the content is usually 70% by volume or less, preferably 50% by volume or less, and more preferably 40% by volume or less, from the viewpoint of maintaining an appropriate viscosity of the nonaqueous electrolyte solution, avoiding a decrease in electrical conductivity, suppressing an increase in negative electrode resistance, and ensuring good large-current discharge characteristics of the nonaqueous electrolyte battery.

[0074] [1-4-5. Cyclic ether compounds] Examples of the cyclic ether compound include cyclic ethers having 3 to 6 carbon atoms, such as tetrahydrofuran, 2-methyltetrahydrofuran, 3-methyltetrahydrofuran, 1,3-dioxane, 2-methyl-1,3-dioxane, 4-methyl-1,3-dioxane, and 1,4-dioxane. Some of the hydrogen atoms in the cyclic ether compound may be substituted with fluorine atoms. Among these, tetrahydrofuran, 1,3-dioxane, 1,4-dioxane, and the like are preferred from the viewpoint of providing high ionic conductivity.

[0075] When the non-aqueous electrolyte solution contains a cyclic ether compound, its content is arbitrary as long as it does not impair the effects of the present invention. However, it is usually 1% by volume or more, preferably 2% by volume or more, more preferably 3% by volume or more, and usually 30% by volume or less, preferably 25% by volume or less, more preferably 20% by volume or less, based on the total amount of non-aqueous solvent in the non-aqueous electrolyte solution. The content of the cyclic ether compound within the above range is likely to ensure the improvement in the degree of dissociation of metal ions, particularly lithium ions, and the improvement in ionic conductivity due to the reduced viscosity of the non-aqueous electrolyte solution. Furthermore, when the negative electrode active material is a carbon-based material, the phenomenon of co-insertion of chain ethers with metal ions, particularly lithium ions, can be suppressed, thereby enabling the input / output characteristics and charge / discharge rate characteristics to be within appropriate ranges.

[0076] [1-4-6. Sulfone compounds] The sulfone compound is not particularly limited and may be a cyclic sulfone or a chain sulfone. In the case of a cyclic sulfone, the carbon number is usually 3 to 6, preferably 3 to 5, and in the case of a chain sulfone, the carbon number is usually 2 to 6, preferably 2 to 5. In addition, the number of sulfonyl groups in one molecule of the sulfone compound is not particularly limited, but is usually 1 or 2. Examples of cyclic sulfones include monosulfone compounds such as trimethylene sulfones, tetramethylene sulfones, and hexamethylene sulfones, and disulfone compounds such as trimethylene disulfones, tetramethylene disulfones, and hexamethylene disulfones. Among these, from the viewpoints of dielectric constant and viscosity, tetramethylene sulfones, tetramethylene disulfones, hexamethylene sulfones, and hexamethylene disulfones are more preferred, and tetramethylene sulfones (sulfolanes) are even more preferred. Preferred sulfolanes are sulfolane and sulfolane derivatives, and preferred sulfolane derivatives are those in which one or more hydrogen atoms bonded to the carbon atoms constituting the sulfolane ring are substituted with a fluorine atom, an alkyl group, or a fluorine-substituted alkyl group. Among these, 2-methylsulfolane, 3-methylsulfolane, 2-fluorosulfolane, 3-fluorosulfolane, 2,3-difluorosulfolane, 2-trifluoromethylsulfolane, 3-trifluoromethylsulfolane, and the like are preferred because they have high ionic conductivity and high input / output.

[0077] Examples of the chain sulfone include dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, monofluoromethyl methyl sulfone, difluoromethyl methyl sulfone, trifluoromethyl methyl sulfone, pentafluoroethyl methyl sulfone, etc. Among these, dimethyl sulfone, ethyl methyl sulfone, and monofluoromethyl methyl sulfone are preferred in terms of improving the high-temperature storage stability of the nonaqueous electrolyte solution. When the non-aqueous electrolyte solution contains a sulfone-based compound, the content thereof is arbitrary as long as it does not impair the effects of the present invention. From the viewpoint of improving high-temperature storage stability, however, the content thereof is usually 0.3 vol% or more, preferably 0.5 vol% or more, more preferably 1 vol% or more, relative to the total amount of the non-aqueous solvent in the non-aqueous electrolyte solution, and is usually 40 vol% or less, preferably 35 vol% or less, more preferably 30 vol% or less.

[0078] [1-5. Auxiliaries] The non-aqueous electrolyte solution of the present invention may contain various auxiliary agents within the range that does not impair the effects of the present invention. As the auxiliary agent, any conventionally known agent can be used. The auxiliary agent can be used alone or in combination of two or more types in any ratio. Examples of the auxiliary include cyclic carbonates having a carbon-carbon unsaturated bond, compounds having an isocyanate group, organic compounds having an isocyanuric acid skeleton, sulfur-containing organic compounds other than the compounds described above, phosphorus-containing organic compounds other than the compounds described above, silicon-containing compounds, aromatic compounds, organic compounds having a cyano group, carboxylic acid anhydrides, boron-containing organic compounds other than the compounds described above, etc. Examples include compounds described in WO 2015 / 111676.

[0079] The content of the auxiliary agent is not particularly limited and may be any amount as long as it does not significantly impair the effects of the present invention, but is usually 0.001% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and is usually 10% by mass or less, preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 1% by mass or less, and particularly preferably less than 1% by mass, relative to the total amount of the nonaqueous electrolyte solution.

[0080] [2.Nonaqueous electrolyte battery] The nonaqueous electrolyte battery of the present invention is a nonaqueous electrolyte battery comprising a positive electrode having a positive electrode active material capable of absorbing and releasing metal ions, and a negative electrode having a negative electrode active material capable of absorbing and releasing metal ions, and is characterized by comprising the nonaqueous electrolyte of the present invention. It is also possible to mix the non-aqueous electrolyte solution of the present invention with other non-aqueous electrolyte solutions within the scope of the present invention. Examples of the nonaqueous electrolyte battery of the present invention include polyvalent cation batteries, metal-air secondary batteries, and secondary batteries using s-block metals other than those mentioned above. Nonaqueous electrolyte secondary batteries are preferred, and lithium ion secondary batteries are more preferred.

[0081] [2-1. Non-aqueous electrolyte] The nonaqueous electrolyte solution used is the nonaqueous electrolyte solution described above. Note that, within the scope of the present invention, other nonaqueous electrolyte solutions may be mixed with the nonaqueous electrolyte solution of the present invention.

[0082] [2-2. Positive electrode] The positive electrode has a positive electrode active material capable of absorbing and desorbing metal ions on at least a portion of the surface of a current collector. The positive electrode active material is preferably a positive electrode active material capable of absorbing and desorbing lithium ions, and preferably contains a lithium transition metal compound.

[0083] [2-2-1. Positive electrode active material] The positive electrode active material (lithium transition metal compound) used in the positive electrode will be described below.

[0084] [2-2-1-1. Lithium transition metal compounds] The lithium transition metal compound is a compound having a structure capable of desorbing and inserting lithium ions, and examples thereof include sulfides, phosphate compounds, silicate compounds, borate compounds, lithium transition metal composite oxides, etc. Among these, phosphate compounds or lithium transition metal composite oxides are preferred, and lithium transition metal composite oxides are more preferred. Examples of lithium transition metal composite oxides include those having a spinel structure that allows three-dimensional diffusion and those having a layered structure that allows two-dimensional diffusion of lithium ions.

[0085] A lithium transition metal composite oxide having a spinel structure is generally represented by the following formula (1). Li x M2O4(1) (In formula (1), x is 1≦x≦1.5, and M represents one or more transition metal elements.) Specific examples of the oxide represented by formula (1) include LiMn2O4, LiCoMnO4, and LiNi 0.5 Mn 1.5 O4, LiCoVO4, etc.

[0086] A lithium transition metal composite oxide having a layered structure is generally represented by the following composition formula (2). Li 1+y MO2(2) (In formula (2), y is −0.1≦y≦0.5, and M represents one or more transition metal elements.) Specific examples of oxides represented by formula (2) include LiCoO2, LiNiO2, and LiNi 0.85 Co 0.10 Al 0.05 O2, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.33 Co 0.33 Mn 0.33 O2, Li 1.05 Ni 0.33 Co 0.33 Mn 0.33 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, Li 1.05 Ni 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.91 Co 0.06 Mn 0.03 O2, LiNi 0.91 Co 0.06 Al 0.03 O2, LiNi 0.90 Co 0.03 Al 0.07 O2, Li 1.05 Ni0.34 Co 0.33 Mn 0.33 O2, Li 1.00 Ni 0.61 Co 0.20 Mn 0.19 Examples include O2.

[0087] Among these, from the viewpoint of improving battery capacity, lithium transition metal composite oxides having a layered structure are preferred, and lithium transition metal composite oxides represented by the following formula (3) are more preferred. Li a1 Ni b1 M c1 O2(3) (In formula (3), a1, b1, and c1 are 0.90≦a1≦1.10, 0.30≦b1≦0.98, and 0.02≦c1≦0.70, respectively, and b1+c1=1. M represents at least one element selected from the group consisting of Co, Mn, Al, Mg, Zr, Fe, Ti, and Er.) In formula (3), b1 is preferably 0.40 or more, more preferably 0.50 or more, and particularly preferably 0.60 or more.

[0088] In particular, from the viewpoint of the structural stability of the lithium transition metal composite oxide, a lithium transition metal composite oxide represented by the following formula (4) is preferred. Li a2 Ni b2 Co c2 M d2 O2(4) (In formula (4), a2, b2, c2, and d2 are 0.90≦a2≦1.10, 0.30≦b2≦0.98, 0.01≦c2≦0.70, and 0.01≦d2≦0.70, respectively, and b2+c2+d2=1. M represents at least one element selected from the group consisting of Mn, Al, Mg, Zr, Fe, Ti, and Er.) In the above formula (4), b2 is preferably 0.40 or more, more preferably 0.50 or more, and particularly preferably 0.60 or more, and d2 is preferably 0.01 or more, more preferably 0.10 or more. Suitable examples of the lithium transition metal composite oxide represented by the above formula (4) include LiNi 0.85 Co0.10 Al 0.05 O2, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.91 Co 0.06 Mn 0.03 O2, LiNi 0.91 Co 0.06 Al 0.03 O2, LiNi 0.90 Co 0.03 Al 0.07 O2, Li 1.00 Ni 0.61 Co 0.20 Mn 0.19 O2, Li 1.05 Ni 0.34 Co 0.33 Mn 0.33 Examples include O2.

[0089] In the above formulas (1) to (3), from the viewpoint of increasing the structural stability of the lithium transition metal composite oxide and suppressing structural deterioration during repeated charge and discharge, M preferably contains Mn or Al, and more preferably Mn. In the above formula (4), from the viewpoint of increasing the structural stability of the lithium transition metal composite oxide and suppressing structural deterioration during repeated charge and discharge, M preferably contains Mn or Al, and more preferably contains Mn.

[0090] [2-2-1-2. Introduction of different elements] The lithium transition metal composite oxide may also contain elements (foreign elements) other than the elements contained in any of the above formulas (1) to (4).

[0091] The positive electrode active material excluding the lithium transition metal compound is not particularly limited as long as it is a positive electrode active material that can absorb and release metal ions, and known positive electrode active materials can be used.

[0092] [2-2-1-3. Surface coating] The positive electrode may be one in which a substance (surface-adhering substance) having a different composition from the positive electrode active material is attached to the surface of the positive electrode active material. Examples of the surface-attaching substance include oxides such as aluminum oxide, sulfates such as lithium sulfate, carbonates such as lithium carbonate, etc. These surface-attaching substances can be attached to the surface of the positive electrode active material, for example, by dissolving or suspending them in a solvent, adding them to the positive electrode active material by impregnation, and drying them. The amount of the surface-adhering substance is preferably 1 μmol / g or more, more preferably 10 μmol / g or more, and usually preferably 1 mmol / g or less, relative to the positive electrode active material. In this specification, a positive electrode active material having the above-mentioned surface-adhering substance attached to its surface is also referred to as a "positive electrode active material."

[0093] [2-2-1-4. Blend] The positive electrode active material may be used alone or in combination of two or more kinds in any ratio.

[0094] [2-2-2. Positive electrode structure and manufacturing method] The positive electrode using the positive electrode active material can be manufactured by a conventional method. That is, the positive electrode active material and a binder, and optionally a conductive material and a thickener, are mixed in a dry state to form a sheet, which is then pressed onto the positive electrode current collector, or these materials are dissolved or dispersed in a liquid medium such as an aqueous solvent or an organic solvent to form a slurry, which is then applied to the positive electrode current collector and dried to form a positive electrode active material layer on the current collector. A positive electrode can also be obtained by a coating method. For example, the positive electrode active material may be roll-molded into a sheet electrode, or may be compression-molded into a pellet electrode. Hereinafter, the case where the slurry is sequentially applied to the positive electrode current collector and then dried will be described.

[0095] [2-2-2-1. Content of positive electrode active material] The content of the positive electrode active material in the positive electrode active material layer is usually 80% by mass or more and 99.5% by mass or less.

[0096] [2-2-2-2. Electrode density] The positive electrode active material layer obtained by coating and drying is preferably compacted by a hand press, a roller press, or the like in order to increase the packing density of the positive electrode active material. The density of the positive electrode active material layer present on the current collector is usually 1.5 g / cm. 3 More than 4.5g / cm 3 The following is the result.

[0097] [2-2-2-3.Conductive materials] Any known conductive material can be used as the conductive material. Specific examples include metal materials such as copper and nickel; graphite such as natural graphite and artificial graphite; carbon black such as acetylene black; and carbon-based materials such as amorphous carbon such as needle coke. The conductive material can be used alone or in combination of two or more types in any ratio. The conductive material is typically used so that it is contained in the positive electrode active material layer in an amount of 0.01% by mass to 50% by mass.

[0098] [2-2-2-4. Binder] When forming the positive electrode active material layer by a coating method, the binder used in producing the positive electrode active material layer is not particularly limited as long as it is a material that can be dissolved or dispersed in a liquid medium for the slurry. For example, in view of weather resistance, chemical resistance, heat resistance, flame retardancy, etc., fluorine-based resins such as polyvinyl fluoride, polyvinylidene fluoride, polytetrafluoroethylene, etc.; CN group-containing polymers such as polyacrylonitrile, polyvinylidene cyanide, etc. are preferred. Also usable are mixtures, modified products, derivatives, random copolymers, alternating copolymers, graft copolymers, block copolymers, etc. The binder may be used alone or in combination of two or more kinds in any ratio. Furthermore, when a resin is used as a binder, the weight-average molecular weight of the resin is optional as long as it does not impair the effects of the present invention, and is usually from 10,000 to 3,000,000. When the molecular weight is in this range, the strength of the electrode is improved, and the electrode can be suitably formed. The content of the binder in the positive electrode active material layer is usually 0.1% by mass or more and 80% by mass or less.

[0099] [2-2-2-5. Current collector] The material of the positive electrode current collector is not particularly limited, and any known material can be used. Specific examples include metal materials such as aluminum, stainless steel, nickel plating, titanium, and tantalum, with aluminum being preferred. The current collector may be in the form of a metal foil, a metal cylinder, a metal coil, a metal plate, a metal thin film, an expanded metal, a punched metal, a foamed metal, or the like. Among these, a metal foil or a metal thin film is preferred. The metal thin film may be suitably formed into a mesh shape. When the current collector of the positive electrode is in the form of a plate or film, the thickness of the current collector is optional, but is usually 1 μm or more and 1 mm or less.

[0100] [2-2-2-6. Thickness of the positive electrode plate] The thickness of the positive electrode plate is not particularly limited, but from the viewpoint of high capacity and high output, the thickness of the positive electrode active material layer obtained by subtracting the thickness of the current collector from the thickness of the positive electrode plate is usually 10 μm or more and 500 μm or less on one side of the current collector.

[0101] [2-2-2-7. Surface coating of positive electrode plate] The positive electrode plate may have a substance of a different composition from the positive electrode plate attached to its surface, and the substance may be the same as the surface-attached substance that may be attached to the surface of the positive electrode active material.

[0102] [2-3. Negative electrode] The negative electrode has a negative electrode active material on at least a portion of the surface of a current collector. [2-3-1. Negative electrode active material] The negative electrode active material used in the negative electrode is not particularly limited as long as it can electrochemically absorb and release metal ions. Specific examples include (i) carbon-based materials, (ii) particles containing metal elements and / or metalloid elements that can be alloyed with Li, (iii) lithium-containing metal composite oxide materials, and (iv) mixtures thereof. Among these, the use of (i) carbon-based materials, (ii) particles containing metal elements and / or metalloid elements that can be alloyed with Li, and (v) mixtures of particles containing metal elements and / or metalloid elements that can be alloyed with Li and graphite particles is preferred, in terms of good cycle characteristics and safety, as well as excellent continuous charge characteristics. These may be used alone or in combination of two or more in any ratio.

[0103] [2-3-1-1. Carbon-based materials] (i) Examples of carbonaceous materials include natural graphite, artificial graphite, amorphous carbon, carbon-coated graphite, graphite-coated graphite, and resin-coated graphite. Of these, natural graphite is preferred. The carbonaceous materials can be used alone or in combination of two or more in any ratio. Examples of natural graphite include scaly graphite, flake graphite, and / or graphite particles obtained by subjecting such graphite to treatment such as spheroidization or densification. Among these, spherical or ellipsoidal graphite particles that have been subjected to spheroidization treatment are preferred from the viewpoint of particle packing properties or charge / discharge rate characteristics. The volume average particle diameter (d50) of the graphite particles is usually 1 μm or more and 100 μm or less.

[0104] [2-3-1-2. Physical properties of carbon-based materials] The carbonaceous material as the negative electrode active material preferably satisfies at least one of the characteristics such as physical properties and shape shown in the following items (1) to (4), and more preferably satisfies several items at the same time. (1) X-ray diffraction parameters The d value (interlayer distance) of the lattice plane (002 plane) of carbon-based materials determined by X-ray diffraction using the Gakushin method is usually 0.335 nm or more and 0.360 nm or less. Also, the crystallite size (Lc) of carbon-based materials determined by X-ray diffraction using the Gakushin method is 1.0 nm or more. (2) Volume-based average particle size The volume-based average particle size of the carbon-based material is the volume-based average particle size (median diameter) determined by a laser diffraction / scattering method, and is usually 1 μm or more and 100 μm or less. (3) Raman R value, Raman half-width The Raman R value of a carbon-based material is a value measured using argon ion laser Raman spectroscopy, and is usually 0.01 or more and 1.5 or less. In addition, the 1580 cm -1 The Raman half-width in the vicinity is not particularly limited, but is usually 10 cm -1 More than 100cm -1 The following is the result. (4) BET specific surface area The BET specific surface area of ​​a carbon-based material is the value of the specific surface area measured using the BET method, and is usually 0.1 m 2 ·g -1 More than 100m 2 ·g -1 The following is the result. The negative electrode active material may contain two or more carbonaceous materials with different properties, where the properties refer to one or more characteristics selected from the group consisting of X-ray diffraction parameters, volume-based average particle size, Raman R value, Raman half-width, and BET specific surface area. Examples of containing two or more carbon-based materials with different properties include a case where the volume-based particle size distribution is not symmetrical about the median diameter, a case where two or more carbon-based materials with different Raman R values ​​are contained, and a case where X-ray parameters are different.

[0105] [2-3-1-3. Materials containing metallic and / or semi-metallic elements that can be alloyed with Li] (ii) Materials containing metallic elements and / or metalloid elements that can be alloyed with Li can be any of those known in the art. However, from the viewpoints of capacity and cycle life, for example, it is preferable that they are metals or metalloids selected from the group consisting of Sb, Si, Sn, Al, As, and Zn. Further, when the material containing metallic elements and / or metalloid elements that can be alloyed with Li contains two or more kinds of metals, the material may be an alloy material composed of an alloy of these metals. Examples of the compound containing metallic elements and / or metalloid elements that can be alloyed with Li include oxides, nitrides, carbides, etc. of metals and / or metalloids. The compound may contain two or more kinds of metallic elements and / or metalloid elements that can be alloyed with Li. Among these, metallic Si (hereinafter also referred to as "Si") or Si-containing inorganic compounds are preferable from the viewpoint of achieving high capacity. In this specification, Si or Si-containing inorganic compounds are collectively referred to as Si compounds. Further, the compound containing metallic elements and / or metalloid elements that can be alloyed with Li may already be alloyed with Li at the time of manufacturing the negative electrode described later. As the compound, Si compounds are preferable from the viewpoint of achieving high capacity. Examples of Si compounds include SiO x1 (0 ≦ x1 ≦ 2), etc. Examples of the metal compound alloyed with Li include Li z1 Si (0 < z1 ≦ 4.4), Li 2z2 SiO 2+z2 (0 < z2 ≦ 2), etc. Examples of Si compounds include Si oxides (SiO x2 , 0 < x2 ≦ 2), which are preferable because their theoretical capacity is larger than that of graphite. Also, amorphous Si or nano-sized Si crystals are preferable because alkali ions such as lithium ions can easily enter and exit, and high capacity can be obtained. When the material containing metallic elements and / or metalloid elements that can be alloyed with Li is in a particulate form, the volume average particle diameter (d50) of the particles is usually 0.01 μm or more and 10 μm or less from the viewpoint of cycle life.

[0106] [2-3-1-4. Mixture of natural graphite and material containing metallic and / or semi-metallic elements that can be alloyed with Li] (v) The mixture of graphite particles and a material containing a metal element and / or a metalloid element that can be alloyed with Li may be a mixture in which the material containing a metal element and / or a metalloid element that can be alloyed with Li and the graphite particles are mixed in the form of independent particles, or it may be a composite in which particles containing a metal element and / or a metalloid element that can be alloyed with Li are present on the surface or inside of graphite particles. The content of the particles containing metal elements and / or metalloid elements that can be alloyed with Li relative to the total of the particles containing metal elements and / or metalloid elements that can be alloyed with Li and the graphite particles is usually 1% by mass or more and 99% by mass or less.

[0107] [2-3-1-5. Lithium-containing metal composite oxide materials] (iii) The lithium-containing metal composite oxide material is not particularly limited as long as it can absorb and release lithium ions. Specifically, from the viewpoint of high current density charge / discharge characteristics, a lithium-containing metal composite oxide material containing titanium is preferred, a composite oxide of lithium and titanium (hereinafter also referred to as "lithium-titanium composite oxide") is more preferred, and a lithium-titanium composite oxide having a spinel structure is even more preferred because it significantly reduces output resistance. Furthermore, the lithium and / or titanium of the lithium titanium composite oxide may be substituted with another metal element, for example, at least one element selected from the group consisting of Al, Ga, Cu, and Zn. As a lithium titanium composite oxide, Li 4 / 3 Ti 5 / 3 O4, Li1Ti2O4 and Li 4 / 5 Ti 11 / 5 O4 is preferred. In addition, examples of lithium titanium composite oxides in which part of lithium and / or titanium is substituted with other elements include Li 4 / 3 Ti 4 / 3 Al 1 / 3 O4 is also preferred.

[0108] [2-3-2. Negative electrode structure and manufacturing method] The negative electrode may be produced by any known method as long as it does not impair the effects of the present invention. For example, the negative electrode may be produced by adding a binder, a liquid medium such as an aqueous solvent or an organic solvent, and, if necessary, a thickener, a conductive material, a filler, etc. to the negative electrode active material to form a slurry, which is then applied to a current collector, dried, and pressed to form a negative electrode active material layer.

[0109] [2-3-2-1. Content of negative electrode active material] The content of the negative electrode active material in the negative electrode active material layer is usually 80% by mass or more and 99.5% by mass or less.

[0110] [2-3-2-2. Electrode density] The negative electrode active material layer obtained by coating and drying is preferably compacted by a hand press, a roller press or the like in order to increase the packing density of the negative electrode active material. The electrode structure when the negative electrode active material is made into an electrode is not particularly limited, but the density of the negative electrode active material layer existing on the current collector is usually 1 g / cm 3 More than 2.2g / cm 3 The following is the result.

[0111] [2-3-2-3. Thickener] Thickeners are usually used to adjust the viscosity of the slurry. Examples of thickeners include, but are not limited to, carboxymethyl cellulose and its salts, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, etc. These may be used alone or in any combination of two or more in any ratio. When a thickener is used, the content of the thickener relative to the negative electrode active material is usually 0.1% by mass or more and 5% by mass or less.

[0112] [2-3-2-4. Binder] The binder for binding the negative electrode active material is not particularly limited as long as it is a material that is stable in the non-aqueous electrolyte solution and the liquid medium used in producing the electrode. Specific examples thereof include rubber-like polymers such as styrene-butadiene rubber (SBR), isoprene rubber, butadiene rubber, fluororubber, acrylonitrile-butadiene rubber (NBR), and ethylene-propylene rubber, as well as fluorine-based polymers such as polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and tetrafluoroethylene-ethylene copolymers. These may be used alone or in combination of two or more in any ratio. The content of the binder relative to the negative electrode active material is usually 0.1% by mass or more and 20% by mass or less. In particular, when the binder contains a rubber-like polymer such as SBR as a main component, the content of the binder relative to the negative electrode active material is usually 0.1% by mass to 5% by mass, and when the binder contains a fluorine-based polymer such as polyvinylidene fluoride as a main component, the content of the binder relative to the negative electrode active material is usually 1% by mass to 15% by mass.

[0113] [2-3-2-5. Current collector] Any known current collector can be used to support the negative electrode active material. Examples of the negative electrode current collector include metal materials such as aluminum, copper, nickel, stainless steel, and nickel-plated steel, but copper is particularly preferred from the standpoints of ease of processing and cost. The negative electrode current collector may be in the form of a metal foil, a metal cylinder, a metal coil, a metal plate, a metal thin film, an expanded metal, a punched metal, a foamed metal, or the like. Among these, a metal foil or a metal thin film is preferred. The metal thin film may be suitably formed into a mesh shape. When the negative electrode current collector is in the form of a plate or film, the thickness of the current collector is not limited, but is usually 1 μm or more and 1 mm or less.

[0114] [2-3-2-6. Thickness of negative electrode plate] The thickness of the negative electrode (negative electrode plate) is designed to match the positive electrode (positive electrode plate) to be used and is not particularly limited, but the thickness of the negative electrode active material layer, obtained by subtracting the thickness of the current collector from the thickness of the negative electrode material, is usually 15 μm or more and 300 μm or less.

[0115] [2-3-2-7. Surface coating of negative electrode plate] The negative electrode plate may have a surface to which a substance (surface-attached substance) having a different composition from the negative electrode active material is attached. Examples of the surface-attached substance include oxides such as aluminum oxide, sulfates such as lithium sulfate, and carbonates such as lithium carbonate.

[0116] [2-4. Separator] A separator is usually interposed between the positive electrode and the negative electrode to prevent short circuits, and in this case, the non-aqueous electrolyte is usually impregnated into the separator before use. There are no particular restrictions on the material or shape of the separator, and any known material can be used as long as it does not impair the effects of the present invention.

[0117] [2-5.Battery design] [2-5-1. Electrode group] The electrode group may have either a laminated structure of the positive electrode plate and the negative electrode plate sandwiched between the separator, or a structure of the positive electrode plate and the negative electrode plate spirally wound with the separator sandwiched between them. The ratio of the volume of the electrode group to the internal volume of the battery (electrode group occupancy rate) is usually 40% to 90%.

[0118] [2-5-2. Current collection structure] When the electrode group has the aforementioned laminated structure, a structure in which the metal core portions of each electrode layer are bundled and welded to a terminal is preferably used. A structure in which multiple terminals are provided within the electrode to reduce resistance is also preferably used. When the electrode group has the aforementioned wound structure, the internal resistance can be reduced by providing multiple lead structures on each of the positive electrode and negative electrode and bundling them to a terminal.

[0119] [2-5-3.Protection elements] The protective element may be a PTC (Positive Temperature Coefficient) element whose resistance increases with heat generation due to excessive current, a thermal fuse, a thermistor, or a valve (current cutoff valve) that cuts off the current flowing in the circuit due to a sudden rise in the internal pressure or temperature of the battery when abnormal heat is generated. It is preferable to select the above protective element so that it will not operate under normal use at high current, and it is even more preferable to design it so that abnormal heat generation or thermal runaway does not occur even without the protective element.

[0120] [2-5-4. Exterior body] A non-aqueous electrolyte battery is generally constructed by housing the non-aqueous electrolyte of the present invention, a negative electrode, a positive electrode, a separator, etc. in an exterior body (exterior case). There are no limitations on this exterior body, and any known exterior body can be used as long as it does not impair the effects of the present invention. The material of the outer case is not particularly limited as long as it is stable against the nonaqueous electrolyte solution used, but from the viewpoints of weight reduction and cost, metals such as iron, aluminum, and aluminum alloys, or laminate films are preferably used. Iron is particularly preferred from the viewpoint of pressure resistance required to operate the current cutoff valve. Examples of exterior cases using the above metals include those in which metals are welded together by laser welding, resistance welding, or ultrasonic welding to form a sealed, airtight structure, and those in which the above metals are used via a resin gasket to form a crimped structure.

[0121] [2-5-5. Shape] The shape of the exterior case may also be arbitrary, and may be, for example, cylindrical, rectangular, laminated, coin-shaped, large, or the like. [Example]

[0122] EXAMPLES The present invention will be explained in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0123] The compounds used in this example are shown below. Compound (A): Vinyl ethylene sulfite

[0124] [ka]

[0125] LiPO2F2: Lithium difluorophosphate LiSO3F: Lithium fluorosulfonate LiBOB: Lithium bis(oxalato)borate VC: vinylene carbonate PRES: 1-propene-1,3-sultone VEC: Vinyl ethylene carbonate

[0126] <Examples 1-1 to 1-3, Comparative Examples 1-1 to 1-13> (Preparation of non-aqueous electrolyte) Under a dry argon atmosphere, thoroughly dried LiPF was dissolved in a mixture of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate (volume ratio 3:4:3) to a concentration of 1.0 mol / L (12.3 mass%) in the nonaqueous electrolyte solution. Vinyl ethylene sulfite (VES) as compound (A) and an anion-containing compound (B) were further dissolved in the nonaqueous electrolyte solution to the contents listed in Table 1. Using this nonaqueous electrolyte solution, nonaqueous electrolyte secondary batteries were fabricated by the following method. Note that in Comparative Examples 1-1, 1-3, 1-5, and 1-7, compound (A) was not used; in Comparative Examples 1-1 and 1-2, anion-containing compound (B) was not used; and in Comparative Examples 1-9 and 1-10, VC and PRES were used instead of the anion-containing compound (B), respectively. In Comparative Examples 1-11 to 1-13, VC, VEC, or ES was further added to the electrolyte solution of Comparative Example 1-7.

[0127] (Preparation of positive electrode) Lithium cobalt nickel manganese oxide (Li 1.05 Ni 0.34 Co 0.33 Mn 0.3385 parts by mass of O2, 10 parts by mass of acetylene black as a conductive material, and 5 parts by mass of polyvinylidene fluoride (PVdF) as a binder were mixed in N-methyl-2-pyrrolidone to form a slurry. This was uniformly applied to a 15 μm thick aluminum foil, dried, and then roll-pressed to form a positive electrode. The density of the positive electrode active material layer in the positive electrode was 2.6 g / cm. 3 It was.

[0128] (Preparation of negative electrode) 49 parts by mass of graphite powder as the negative electrode active material, 50 parts by mass of an aqueous dispersion of sodium carboxymethylcellulose (concentration of sodium carboxymethylcellulose: 1% by mass) as a thickener, and 1 part by mass of an aqueous dispersion of styrene-butadiene rubber (concentration of styrene-butadiene rubber: 49% by mass) as a binder were mixed in a disperser to form a slurry. The obtained slurry was uniformly applied to a 10 μm thick copper foil, dried, and then roll-pressed to form a negative electrode. The density of the negative electrode active material layer in the negative electrode was 1.35 g / cm. 3 It was.

[0129] (Manufacturing of non-aqueous electrolyte secondary batteries) The positive electrode, negative electrode, and polyolefin separator prepared above were stacked in this order, and the resulting battery element was wrapped in an aluminum laminate film, and the nonaqueous electrolyte solution was poured into the laminate, followed by vacuum sealing to prepare a sheet-shaped nonaqueous electrolyte secondary battery.

[0130] [Evaluation of non-aqueous electrolyte secondary batteries] The nonaqueous electrolyte secondary batteries prepared above were evaluated as follows.

[0131] (Initial charge / discharge) In a thermostatic bath at 25°C, the sheet-shaped nonaqueous electrolyte secondary battery was charged at a constant current equivalent to 0.025 C up to 3.6 V, then constant current-constant voltage charged at 0.167 C up to a voltage of 4.2 V (hereinafter also referred to as "CC-CV charging"), and then discharged at a constant current of 0.167 C down to 2.5 V. The nonaqueous electrolyte secondary battery was then stabilized by CC-CV charging at 0.167 C to 4.1 V and then stored at 60 °C for 12 hours. It was then discharged at a constant current of 0.167 C to 2.5 V at 25 °C, followed by CC-CV charging at 0.167 C to 4.2 V. It was then discharged at a constant current of 0.167 C to 2.5 V, and the battery capacity at this point was recorded as the initial capacity. It was then CC-CV charged at 0.2 C to 4.2 V, completing the initial charge / discharge. Here, 1C represents the current value that discharges the battery's reference capacity in 1 hour, and for example, 0.025C represents 1 / 40 of that current value.

[0132] (Evaluation of recovery capacity maintenance rate) The nonaqueous electrolyte secondary battery, after initial charge / discharge, was left standing at 60°C for two weeks. After standing for two weeks, it was discharged at a constant current of 0.167 C to 2.5 V at 25°C, and then CC-CV charged at 0.167 C to a voltage of 4.2 V. It was then discharged at a constant current of 0.167 C to 2.5 V, and the battery capacity at this time was taken as the recovered capacity. [(recovered capacity / initial capacity) × 100] was taken as the recovered capacity retention rate. Table 1 shows the recovered capacity retention rates relative to the value of the nonaqueous electrolyte secondary battery (Comparative Example 1-1) not containing compound (A) and a specific amount of anion-containing compound (B), which is set to 100. Note that a larger recovered capacity retention rate is preferable.

[0133] [Table 1]

[0134] From Table 1, it can be seen that the non-aqueous electrolyte secondary batteries (Examples 1-1 to 1-3) containing the compound (A) and a specific amount of the anion-containing compound (B) in the non-aqueous electrolyte solution have the following characteristics: (a) A non-aqueous electrolyte secondary battery (Comparative Example 1-1) in which the non-aqueous electrolyte does not contain the compound (A) and the anion-containing compound (B), (b) A non-aqueous electrolyte secondary battery (Comparative Example 1-2) in which the non-aqueous electrolyte contains the compound (A) but does not contain the anion-containing compound (B); (c) Non-aqueous electrolyte secondary batteries in which the non-aqueous electrolyte does not contain the compound (A) but contains the anion-containing compound (B) (Comparative Examples 1-3, 1-5, and 1-7), (d) Non-aqueous electrolyte secondary batteries in which the non-aqueous electrolyte solution contained compound (A) and anion-containing compound (B) in an amount exceeding a predetermined amount (Comparative Examples 1-4, 1-6, and 1-8); (e) Non-aqueous electrolyte secondary batteries (Comparative Examples 1-9 and 1-10) in which the non-aqueous electrolyte contains materials used in the prior art instead of compound (A) and anion-containing compound (B); and (f) It is understood that the recovered capacity retention rate of the nonaqueous electrolyte battery is improved compared to the nonaqueous electrolyte secondary batteries (Comparative Examples 1-11 to 1-13) containing a specific anion-containing compound and a material used in the prior art. The reason for the improved recovered capacity retention rate of the nonaqueous electrolyte battery of the present invention is believed to be that by combining compound (A) with a specific amount of anion-containing compound (B), compound (A) and anion-containing compound (B) form a hardly soluble and strong co-coating film, which efficiently suppresses side reactions on the electrode surface.

[0135] <Examples 2-1 to 2-2, Comparative Examples 2-1 to 2-5> (Preparation of non-aqueous electrolyte) Under a dry argon atmosphere, thoroughly dried LiPF6 was dissolved in a mixture of ethylene carbonate, dimethyl carbonate, and methyl acetate (volume ratio 3:4:3) to give a concentration of 1.0 mol / L (12.5 mass%) in the nonaqueous electrolyte solution, and compound (A) and anion-containing compound (B) were further dissolved therein to prepare nonaqueous electrolyte solutions with the contents shown in Table 2. Note that in Comparative Examples 2-2 to 2-4, compound (A) was not used, and in Comparative Examples 2-1 to 2-2, anion-containing compound (B) was not used. Furthermore, using this nonaqueous electrolyte solution, nonaqueous electrolyte secondary batteries were fabricated in the same manner as in Example 1-1.

[0136] [Evaluation of non-aqueous electrolyte secondary batteries] The non-aqueous electrolyte secondary batteries prepared above were evaluated as follows.

[0137] (Initial charge / discharge) In a thermostatic bath at 25°C, a sheet-shaped non-aqueous electrolyte secondary battery was charged at a constant current of 0.025C up to 3.6V, then CC-CV charged at 0.167C up to a voltage of 4.2V, and then discharged at a constant current of 0.167C down to 2.5V. The nonaqueous electrolyte secondary battery was then stabilized by CC-CV charging at 0.167 C to 4.1 V and then stored at 60°C for 12 hours. It was then discharged at a constant current of 0.167 C to 2.5 V at 25°C, followed by CC-CV charging at 0.167 C to 4.2 V. It was then discharged at a constant current of 0.167 C to 2.5 V, and the battery capacity at this point was recorded as the initial capacity. It was then CC-CV charged at 0.167 C to 4.2 V, completing the initial charge / discharge.

[0138] (Evaluation of recovery capacity maintenance rate) The recovered capacity retention rate was evaluated in the same manner as in Example 1-1.

[0139] (Evaluation of gas generation rate during high-temperature storage) Before the initial charge / discharge and after evaluation of the recovered capacity retention rate, the nonaqueous electrolyte secondary battery was immersed in an ethanol bath at room temperature and the volume was measured, and the change in volume was taken as the amount of gas generated during high-temperature storage.

[0140] Table 2 shows the evaluation results of the recovered capacity retention rate and the high-temperature storage gas generation rate as shown above, which are the recovered capacity retention rate (a relative value when the recovered capacity retention rate of the battery (Comparative Example 2-1) containing only compound (A) as an additive is set to 100) and the high-temperature storage gas generation rate (a relative value when the high-temperature storage gas generation rate of the battery (Comparative Example 2-1) containing only compound (A) as an additive is set to 100). The lower the high-temperature storage gas generation rate, the better.

[0141] [Table 2]

[0142] From Table 2, even when a part of the chain carbonate in the nonaqueous electrolyte solution of the nonaqueous electrolyte secondary battery was replaced with methyl acetate, the nonaqueous electrolyte secondary batteries (Examples 2-1 to 2-2) in which the nonaqueous electrolyte solution contained the compound (A) and a specific amount of the anion-containing compound (B) (a) A non-aqueous electrolyte secondary battery (Comparative Example 2-2) in which the non-aqueous electrolyte does not contain the compound (A) and the anion-containing compound (B), (b) A non-aqueous electrolyte secondary battery (Comparative Example 2-1) in which the non-aqueous electrolyte contains the compound (A) but does not contain the anion-containing compound (B); (c) Non-aqueous electrolyte secondary batteries in which the non-aqueous electrolyte does not contain compound (A) but contains an anion-containing compound (B) (Comparative Examples 2-3 and 2-4), and (d) It can be seen that the recovered capacity retention rate of the nonaqueous electrolyte battery is improved compared to a nonaqueous electrolyte secondary battery (Comparative Example 2-5) in which the nonaqueous electrolyte contains compound (A) and an amount of anion-containing compound (B) exceeding a predetermined amount. Furthermore, similar comparisons show that the nonaqueous electrolyte secondary batteries (Examples 2-1 to 2-2) in which the nonaqueous electrolyte solution contains compound (A) and a specific amount of anion-containing compound (B) suppress the gas generation rate after high-temperature storage, which becomes an issue when a portion of the chain carbonate in the nonaqueous electrolyte solution of a nonaqueous electrolyte secondary battery is replaced with methyl acetate.

[0143] <Examples 3-1 to 3-2, Comparative Example 3-1> (Preparation of non-aqueous electrolyte) A nonaqueous electrolyte solution was prepared in the same manner as in Example 2-1, except that the ester solvent was methyl propionate and the compound (A) and the anion-containing compound (B) were used in the amounts shown in Table 3. In Comparative Example 3-1, the anion-containing compound (B) was not used. Using this nonaqueous electrolyte solution, a nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 1-1.

[0144] [Evaluation of non-aqueous electrolyte secondary batteries] The nonaqueous electrolyte secondary battery prepared above was evaluated in the same manner as in Example 2-1. Table 3 shows the above evaluation results: recovered capacity retention rate (a relative value when the recovered capacity retention rate of the battery (Comparative Example 3-1) containing only compound (A) as an additive is taken as 100), and high-temperature storage gas generation rate (a relative value when the amount of gas generated from the battery (Comparative Example 3-1) containing only compound (A) as an additive is taken as 100).

[0145] [Table 3]

[0146] Table 3 shows that even when a portion of the chain carbonate in the nonaqueous electrolyte of the nonaqueous electrolyte secondary battery is replaced with methyl propionate, the nonaqueous electrolyte secondary batteries (Examples 3-1 and 3-2) in which the nonaqueous electrolyte contains compound (A) and a specific amount of anion-containing compound (B) have an improved recovered capacity retention rate and a suppressed high-temperature storage gas generation rate, similar to Examples 2-1 and 2-2.

[0147] <Example 4-1, Comparative Examples 4-1 to 4-3> (Preparation of non-aqueous electrolyte) A nonaqueous electrolyte solution was prepared in the same manner as in Example 3-1, except that methyl acetate was used instead of methyl propionate, and compound (A) and anion-containing compound (B) were used in the amounts shown in Table 4. In Comparative Examples 4-2 to 4-3, compound (A) was not used, and in Comparative Examples 4-1 to 4-2, anion-containing compound (B) was not used. Using this nonaqueous electrolyte solution, a nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 1-1.

[0148] [Evaluation of non-aqueous electrolyte secondary batteries] (Initial charge / discharge) The initial charge and discharge was completed in the same manner as in Example 2-1.

[0149] (Initial DCR evaluation test) After initial charging and discharging, the nonaqueous electrolyte secondary battery was subjected to constant current discharge at 0.167 C to 2.5 V at 25°C, followed by CC-CV charging at 0.167 C to 3.7 V. Next, constant current discharge was performed at 0.5 C, 1.0 C, and 1.5 C for 10 seconds each, and the voltage at the 10-second interval was measured. The internal resistance was calculated from this current-voltage line and used as the initial room temperature DCR (direct current resistance). Furthermore, constant current discharge was performed at -10°C for 10 seconds at 0.25C, 0.5C, and 0.75C, and the voltage at the end of the 10 seconds was measured. The internal resistance was calculated from the current-voltage line and used as the initial low-temperature DCR.

[0150] (High temperature storage durability test) The nonaqueous electrolyte secondary battery that underwent the initial low-temperature DCR evaluation test was CC-CV charged at 0.167 C (cut by 0.01 C) at 25°C to 4.2 V, and then left to stand at 60°C for two weeks for high-temperature storage. After that, the battery was sufficiently cooled and then discharged at 25°C at a constant current of 0.167 C to 2.5 V. Next, CC-CV charged at 0.167 C (cut by 0.01 C) to 4.2 V, and then discharged again at 0.167 C to 2.5 V.

[0151] (Evaluation of DCR after high temperature storage) The nonaqueous electrolyte secondary batteries subjected to the high-temperature storage durability test were subjected to constant-current discharge at 0.167 C to 2.5 V at 25°C, followed by CC-CV charging at 0.167 C to 3.7 V. Next, constant-current discharge was performed at 0.5 C, 1.0 C, and 1.5 C for 10 seconds, respectively, and the voltage at 10 seconds was measured. The internal resistance was calculated from this current-voltage curve, and the room-temperature DCR after high-temperature storage was recorded. Furthermore, constant-current discharge was performed at 0.25 C, 0.5 C, and 0.75 C for 10 seconds, respectively, at -10°C, and the voltage at 10 seconds was measured. The internal resistance was calculated from this current-voltage curve, and the low-temperature DCR after storage was calculated. The increase in low-temperature DCR after high-temperature storage was calculated as [low-temperature DCR after storage / initial low-temperature DCR × 100]. As the evaluation results, Table 4 shows the room temperature DCR increase rate after high temperature storage (a relative value when the room temperature DCR after high temperature storage of the battery (Comparative Example 4-1) containing only compound (A) as an additive is taken as 100), and the low temperature DCR increase rate after high temperature storage (a relative value when the low temperature DCR increase rate after high temperature storage of the battery (Comparative Example 4-1) containing only compound (A) as an additive is taken as 100). The smaller the room temperature DCR increase rate after high temperature storage and the lower the low temperature DCR increase rate after high temperature storage, the better.

[0152] [Table 4]

[0153] From Table 4, when a part of the chain carbonate in the nonaqueous electrolyte solution of the nonaqueous electrolyte secondary battery was substituted with methyl acetate, the nonaqueous electrolyte secondary battery (Example 4-1) in which the nonaqueous electrolyte solution contained the compound (A) and the anion-containing compound (B) (a) A non-aqueous electrolyte secondary battery (Comparative Example 4-2) in which the non-aqueous electrolyte did not contain the compound (A) and the anion-containing compound (B), (b) A non-aqueous electrolyte secondary battery (Comparative Example 4-1) in which the non-aqueous electrolyte contains the compound (A) but does not contain the anion-containing compound (B), and (c) It can be seen that the room temperature DCR increase rate and low temperature DCR increase rate of the nonaqueous electrolyte battery after high temperature storage are suppressed compared to the nonaqueous electrolyte secondary battery (Comparative Example 4-3) in which the nonaqueous electrolyte does not contain compound (A) but contains an anion-containing compound (B).

[0154] <Example 5-1, Comparative Example 5-1> (Preparation of non-aqueous electrolyte) A nonaqueous electrolyte solution was prepared in the same manner as in Example 3-1, except that compound (A) and anion-containing compound (B) were used in the amounts shown in Table 5. In Comparative Example 5-1, anion-containing compound (B) was not used. Using this nonaqueous electrolyte solution, a nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 1-1. [Evaluation of non-aqueous electrolyte secondary batteries] The nonaqueous electrolyte secondary battery prepared above was evaluated in the same manner as in Example 4-1. As the evaluation results, Table 5 shows the room temperature DCR increase rate after high temperature storage (a relative value when the room temperature DCR after high temperature storage of the battery (Comparative Example 5-1) containing only compound (A) as an additive is taken as 100), and the low temperature DCR increase rate after high temperature storage (a relative value when the low temperature DCR increase rate after high temperature storage of the battery (Comparative Example 5-1) containing only compound (A) as an additive is taken as 100). The smaller the room temperature DCR increase rate after high temperature storage and the lower the low temperature DCR increase rate after high temperature storage, the better.

[0155] [Table 5]

[0156] Table 5 shows that even when a portion of the chain carbonate in the nonaqueous electrolyte of the nonaqueous electrolyte secondary battery is replaced with methyl propionate, the nonaqueous electrolyte secondary battery (Example 5-1) in which the nonaqueous electrolyte contains compound (A) and anion-containing compound (B) exhibits a suppressed room-temperature DCR increase rate and low-temperature DCR increase rate after high-temperature storage of the nonaqueous electrolyte battery, as in Example 4-1. [Industrial Applicability]

[0157] By using the nonaqueous electrolyte solution of the present invention as an electrolyte for a nonaqueous electrolyte battery, the recovered capacity retention rate of the nonaqueous electrolyte battery can be improved. Therefore, the nonaqueous electrolyte solution of the present invention can be suitably used in all fields, such as electronic devices, in which nonaqueous electrolyte batteries are used. The nonaqueous electrolyte of the present invention and the nonaqueous electrolyte battery using the same can be used in various known applications. Specific examples of applications include notebook computers, pen-input personal computers, mobile personal computers, electronic book players, mobile phones, mobile fax machines, mobile copiers, mobile printers, mobile audio players, small video cameras, headphone stereos, video movie cameras, LCD televisions, handheld vacuum cleaners, portable CD players, minidiscs, transceivers, electronic organizers, calculators, memory cards, portable tape recorders, radios, backup power supplies, motors, automobiles, motorcycles, mopeds, bicycles, lighting equipment, toys, game machines, clocks, power tools, flash devices, cameras, home backup power supplies, business backup power supplies, load-leveling power supplies, and natural energy storage power supplies.

Claims

1. A non-aqueous electrolyte solution comprising a compound (A) represented by formula (I) and one or more anion-containing compounds (B) selected from the group consisting of a phosphate anion-containing compound having a P-F bond and a P=O bond, an anion-containing compound having an S=O bond, and an oxalate complex anion-containing compound, the content of the anion-containing compound (B) being 0.001% by mass or more and 5% by mass or less in the electrolyte solution. 【Chemistry 1】 (In formula (I), X 1 and X 2 each independently represents an oxygen atom or CH 2 and R 1 and R 2 are each independently a hydrogen atom, a halogen atom, or a hydrocarbon group, and n is 1 or 2. 1 and R 2 is a hydrocarbon group containing at least one carbon-carbon unsaturated bond, and when n is 2, X 1 and X 2 At least one of 2 It is.)

2. The nonaqueous electrolyte solution according to claim 1 , wherein the compound (A) is a compound represented by the following formula (II): 【Chemistry 2】 (In formula (II), R 1 and R 2 is R in the formula (I). 1 and R 2 is the same as

3. R 1 and R 2 are each independently one selected from a hydrogen atom, a halogen atom, a vinyl group, and an allyl group; R 1 and R 2 The nonaqueous electrolyte solution according to claim 1 or 2, wherein either one of the groups is selected from a vinyl group and an allyl group.

4. The nonaqueous electrolyte solution according to claim 1 or 2, comprising the compound (A) in an amount of 0.01% by mass or more and 10% by mass or less.

5. The nonaqueous electrolyte solution according to claim 1 or 2, further comprising a chain carboxylate ester.

6. The nonaqueous electrolyte solution according to claim 5 , wherein the chain carboxylate ester is methyl acetate or methyl propionate.

7. The nonaqueous electrolyte solution according to claim 5 , wherein the content of the chain carboxylate in the nonaqueous solvent is from 1 vol % to 70 vol %.

8. 3. A non-aqueous electrolyte battery comprising: a positive electrode having a positive electrode active material capable of absorbing and releasing metal ions; a negative electrode having a negative electrode active material capable of absorbing and releasing metal ions; and the non-aqueous electrolyte according to claim 1 or 2.